The woman Lilith - Cornish, Richard (South Melbourne, Victoria : Macmillan, 1975)
Reimagines the myth of Lilith, portraying her as a complex, rebellious figure who challenges patriarchy, explores themes of gender, power, and identity in ancient and modern contexts.
Keywords: Lilith (Semitic mythology) -- Fiction; Women in literature -- Fiction